Assessment of ability of medical and obstetric students to achieve adequate positive pressure ventilation using basic neonatal resuscitation manikins - Solis-Chimoy, Blanca (2021)
Introduction. The ability to perform adequate positive pressure ventilation is necessary for neonatal clinical practice. However, there are few studies on the achievements of undergraduate students on this task. It is necessary to assess health science students’ adequate positive pressure ventilation because it is vital at the beginning of their clinical activity. Objective. To evaluate the cognitive and procedural ability related to adequate positive pressure ventilation performed by 6th year medicine students and 4th year obstetrics students at a public university in Lima, Peru. Methods. We surveyed 78 medical and obstetric students in their last years of studies within six months of taking a course on neonatal resuscitation that included positive pressure ventilation theory and practice. Participants voluntarily agreed to participate in this study. Previously, we validated the survey by asking three experienced neonatologists for their expert judgments on improving the survey. The survey consists of three theoretical questions as a cognitive assessment and three practice assessment criteria qualified by observing performance using neonatal manikins. Results. Medicine students had a better practical ability (p <0.001) than obstetrics students, and obstetrics students presented better theoretical knowledge (p = 0.019). However, both groups achieved limited performance within six months of taking the neonatal clinical practice course as 21.8% of all students passed both the theoretical and practical parts of this study. Conclusion. Participants from both schools require further training alternatives to achieve adequate positive pressure ventilation performance.